Economics and Insurance - Little, L. T. (Review of Economic Studies, 1937)
Journal Article Economics and Insurance Get access L. T. Little L. T. Little London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 1, October 1937, Pages 32–52, https://doi.org/10.2307/2967578 Published: 01 October 1937